Analisis Penggunaan Media Flashcard terhadap Motivasi Belajar Siswa pada Mata Pelajaran PAI di SD Negeri 15 Selayo - Putri, Yulia; Alfurqan, Alfurqan (Lembaga Yasin AlSys, 2023)
This research is motivated by the use of learning media that is appropriate for use by teachers so that students have motivation in studying the media, namely flashcard media. This study aims to determine the use of flashcard media in Islamic Religious Education subject class 1 at SD Negeri 15 Selayo, to determine the supporting and inhibiting factors of flashcard media on student learning motivation on ablution material in class 1 Islamic Religious Education subject at SD Negeri 15 Selayo and to find out the results of using flashcard media on student learning motivation in the subject of Islamic Religious Education at SD Negeri 15 Selayo. This research uses descriptive qualitative method, the object of this research is the first grade students of SD Negeri 15 Selayo and the subject of this research is students' learning motivation. Then the data obtained from observation, interviews with informants, and documentation to see the existing phenomena. The results of this study indicate that the use of flashcard media in class 1 Islamic Religious Education subject at SD Negeri 15 Selayo is very good to use because it really helps students in motivating students. Students have high enthusiasm and enthusiasm for Islamic religious education lessons so they have a strong determination and will in carrying out learning activities, students have a desire to succeed, there is encouragement and need in learning, there are hopes and aspirations, there is an appreciation in learning, there are interesting activities in learning, the creation of a conducive learning environment. So with this it proves that the results of using flashcard media in learning make students have motivation to learn